The Important of Management Functions in Sustainable MICE - Astawa, I Ketut; Partini, Ni Made Siska; Sari, I Gusti Agung Mas Krisna Komala; Suardani, Anak Agung Putri (Poltanesa, 2024)
This study aims to analyze the importance of management functions in sustainable meetings, incentives, conferences, and exhibition activities at Hotel Indigo Bali Seminyak Beach. The informants in this study were the director of events, assistant director of events, and business development executive who purposively determined. Data collection is carried out through observation, literature study, interviews, group discussions, and documentation. The results reveal that sales teams managed meeting, incentive, conference, and exhibition activities have made significant strides in implementing sustainable practices in various aspects of meetings, incentives, conferences, and exhibitions. Many aspects have been successfully integrated, such as local souvenirs, adoption of renewable energy, electronic registration, and health and safety promotion still need improvement. The gap arises from the scale of events, resource limitations, and technical constraints. A comprehensive analysis of the implementation of sustainable meeting, incentive, conference, and exhibition management functions shows the establishment of strong local community ties, innovation in menu variations, prioritizing environmentally friendly practices, collaborating with local craft entrepreneurs, optimizing technology and social media, maintaining environmentally friendly commitments, and recommending the use of digital-based media in various management functions. The implementation of this management function supports improving the hotel's ability to achieve sustainable meeting, incentive, conference, and exhibition activities.